2015
DOI: 10.1017/s2040174415001439
|View full text |Cite
|
Sign up to set email alerts
|

Review of the importance of nutrition during the first 1000 days: maternal nutritional status and its associations with fetal growth and birth, neonatal and infant outcomes among African women

Abstract: Maternal nutritional status (MNS) is a strong predictor of growth and development in the first 1000 days of life and may influence susceptibility to non-communicable diseases in adulthood. However, the role of nutrition during this window of developmental plasticity in Africa is unclear. This paper reviews published data to address whether maternal nutrition during the first 1000 days is important for Africa, with a focus on MNS and its associations with fetal growth and birth, neonatal and infant outcomes. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 70 publications
3
58
1
2
Order By: Relevance
“…Our results also highlight the need to consider maternal factors when evaluating potentially at‐risk infants. For instance, our observed association between SAM infants and maternal anthropometric deficit on univariate analysis is consistent with other evidence that maternal nutritional status has both short‐ and long‐term associations with infant health (Liu et al, ; Wrottesley, Lamper, & Pisa, ). That supplementing undernourished mothers might have also benefits for their infants is biologically plausible but needs more evidence (Stevens et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Our results also highlight the need to consider maternal factors when evaluating potentially at‐risk infants. For instance, our observed association between SAM infants and maternal anthropometric deficit on univariate analysis is consistent with other evidence that maternal nutritional status has both short‐ and long‐term associations with infant health (Liu et al, ; Wrottesley, Lamper, & Pisa, ). That supplementing undernourished mothers might have also benefits for their infants is biologically plausible but needs more evidence (Stevens et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Although African settings exhibit features typical of the epidemiological transition, such as higher prevalences of maternal overweight and obesity, combined with poor diet quality and multiple micronutrient deficiencies, the majority of trials focus on macro- and micronutrient supplementation in chronically malnourished women [15]. Only one South African study conducted in the Vaal Triangle, which is a semi-industrialised, low-income region, showed that pregnant women were predominantly overweight/obese and consumed diets which were high in energy and refined sugars, low in protein and micronutrients, and lacked diversity [16].…”
Section: Maternal Nutrition and Physical Activity During Pregnancymentioning
confidence: 99%
“…2,3 According to Victora et al and Wrottesly et al the outcomes of maternal and child undernutrition include shorter adult height, and lower birthweight, which are likely to affect growth and development and also susceptibility to NCDs such as cardiovascular disease and diabetes in adulthood. 3,4 Lesotho is one of the poorest countries in the world with high levels of food insecurity. 5 The Food and Agriculture Organization of the United Nations reported that 59% of Basotho households fall below the poverty line while 40% live in extreme poverty and 67% are considered poor.…”
Section: Introductionmentioning
confidence: 99%